Psychometric Evaluation of Instruments Measuring The Older Adult’s Functional Status in Indonesian - Dara Febriana; Juanita Juanita; Nurhasanah Nurhasanah (Jurnal Keperawatan Padjadjaran, 2019)
For year research on quantifying how well individual’s function has been reported. Assessing function is particularly important in the older adults, as the prevalence of functional disability increases with age. In Indonesia, there is a lack of studies that measure the functional status of the older adults. There is even less research on evaluating the psychometric properties of an instrument. Therefore, this study aimed to compare the psychometric properties of the evidence supported functional status instrument consisting of the Short Physical Performance Battery (SPPB), the Functional Status Questionnaire (FSQ) and the Physical Performance Test (PPT). This study using the validation design with descriptive approach. And 401 subjects aged more than 60 years old were recruited purposively from five districts in Aceh. Every instrument showed good validity and reliability and has been used either for research purposes or in clinical setting. All subjects completed the FSQ, SPBB, and FSQ assessment. Correlation between SPPB and PPT were higher than FSQ when assessed for convergent validity the FSQ had comparable correlations with the reported health status. However, relationship between SPPB, PPT and FSQ were inconsistent. The findings of this study is expected to support the psychometric properties of all three instrument for functional status assessment in Indonesian Older adults, and SPPB appear to be the best among the other instruments to use in the nursing practice.